Systemic virus infection results in CD8 T cell recruitment to the retina in the absence of local virus infection - Paskeviciute, Egle; Chen, Mei; Xu, Heping; Honoré, Bent; Vorum, Henrik; Sørensen, Torben Lykke; Christensen, Jan Pravsgaard; Thomsen, Allan Randrup; Nissen, Mogens Holst; Steffensen, Maria Abildgaard (Frontiers in Immunology, 2023)
During recent years, evidence has emerged that immune privileged sites such as the CNS and the retina may be more integrated in the systemic response to infection than was previously believed. In line with this, it was recently shown that a systemic acute virus infection leads to infiltration of CD8 T cells in the brains of immunocompetent mice. In this study, we extent these findings to the neurological tissue of the eye, namely the retina. We show that an acute systemic virus infection in mice leads to a transient CD8 T cell infiltration in the retina that is not directed by viral antigen us infection inside the retina. CD8 T cells were found throughout the retinal tissue, and had a high expression of CXCR6 and CXCR3, as also reported for tissue residing CD8 T cells in the lung and liver. We also show that the pigment epithelium lining the retina expresses CXCL16 (the ligand for CXCR6) similar to epithelial cells of the lung. Thus, our results suggest that the retina undergoes immune surveillance during a systemic infection, and that this surveillance appears to be directed by mechanisms similar to those described for non-privileged tissues.